Efektivitas Program SREGEP Terhadap Kepuasan Pasien Rawat Inap di Rumah Sakit Islam Pati - Supriyanti, Supriyanti; Gero, Sabrina; Pujiyanto, Tri Ismu (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Introduction: The low inpatient satisfaction level at Rumah Sakit Islam Pati, which has not met the minimum service standard of 95%. The research problem focuses on the effectiveness of the SREGEP program (Service Excellent Nurse Movement) in improving patient satisfaction through training in effective two-way communication and the application of the 6S attitude (Smile, Greeting, Addressing, Polite, Courteous, Responsive). Objective: This study aims to analyze the effectiveness of the SREGEP Program in increasing inpatient satisfaction. Method: A quasi-experimental study with a nonequivalent control group pretest-posttest design was conducted on 36 patients and 12 nurses in Class III inpatient units. Total sampling was applied, dividing participants into intervention (SREGEP program) and control (6S program) groups. Result: The results showed a significant increase in the satisfaction score in the intervention group from an average of 68.67 to 95.00 (p=0.001), while the control group increased from 60.66 to 72.83 (p=0.001). Conclusion: The SREGEP program was more effective than the 6S program in enhancing inpatient satisfaction at Rumah Sakit Islam Pati. The study recommends expanding the implementation of the SREGEP program across all hospital units, alongside regular monitoring and evaluation to maintain program effectiveness.